STOCHASTIC AND STATISTICAL METHODS IN HYDROLOGY AND ENVIRONMENTAL ENGINEERING. - Hipel, Keith W., editor (Dordrecht : SPRINGER-SCIENCE+BUSINESS MEDIA, B.V., 1994)
The types of Professionals who may wish to use this book include Water Resource Engineer, Environmental Scientists, Hydrologists, Civil Engineers, Earth Scientists, Geographers, Planners, Statisticians, System Engineers and Management Scientists